Analysis Bachelor of Public Health Needs and Policy Constraints Aspects in the Health Department Konawe District - Syawaluddin, Syawaluddin; Azizi Jayadipraja, Erwin; Kamalia, La Ode (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: The initial survey conducted at the Konawe District Health Office shows that the distribution of Public Health Bachelors has not been evenly distributed until now, where there are still health centers in Konawe District which lack public health personnel. In addition, the management of the duties of the Bachelor of Public Health at the Health center is sometimes not in accordance with the main task. So that researchers intend to conduct research on